Estimasi Populasi dan Karakteristik Habitat Lutung Jawa (Trachypithecus auratus) di Taman Hutan Raya R. Soerjo Jawa Timur - Andrie Ahlul Azmi; Moch Chanan; Nirmala Ayu Aryanti (Universitas Muhammadiyah Malang, 2019)
ABSTRACT Tahura R. Soerjo was declared a major forest area in 1992 which included protected forests of Mount Anjasmoro, Mount Gede, Mount Biru, Mount Limas, and the Arjuno-Lalijiwo nature reserve. In 1997, the area of R. Soerjo's great forest area increased to 27,868.30 hectares, which consisted of 22,908.3 hectares of protected forest, and the Arjuno-Lalijiwo Nature Reserve area of 4,960 hectares. Wild animals are animals that live in natural ecosystems. Wildlife is all animals that live in the wild that are not directly controlled or domesticated by humans. Wildlife management is the art of controlling wildlife habitat and population characteristics and human activities to achieve the desired goals. Wildlife management is part of wildlife conservation efforts.Slim and long-tailed bodied Lutung. Hair color (hair) body varies depending on the species, from black and gray, to golden yellow. When compared to his legs, the Lutung's hands are fairly short, with their hairless soles. Lutung size ranges from 40-80 cm, weighing 5-15 kg; larger-bodied males than females. The protrusion above his eyes distinguishes Lutung from his close relative. The location of the observation is made systematically in the direction of the planned transect line. The point of observation is systematically intended to obtain varied data. By paying attention to the points that have been made in previous years. Based on the results obtained, it can be concluded that there are 3 highest types of INP plants from the tree level, namely Engelhardia spicata, Dampul Ficus lepicarpa, Quercus sundaicus Red Pairs. At the pole level there are Dampul Ficus lepicarpa, Berasan, Engukhardia spicat cucumber while at the sapling level there are Dampul Ficus lepicarpa, Put Buddleja asiantica, Put Red Quercus sundaicus. Each with an average value of 300.